Involvement of Human Papillomaviruses in Cervical Cancer - Wang, Xuelian; Huang, Xiumin; Zhang, Youzhong (Frontiers in Microbiology, 2018)
Human papillomaviruses (HPV) are the first viruses to have been acknowledged to prompt carcinogenesis, and they are linked with cancers of the uterine cervix, anogenital tumors, and head and neck malignancies. This paper examines the structure and primary genomic attributes of HPV and highlights the clinical participation of the primary HPV serotypes, focusing on the roles that HPV-16 and 18 play in carcinogenesis. The mechanisms that take place in the progression of cervical neoplasia are described. The oncogenic proteins E6 and E7 disrupt control of the cell cycle by their communication with p53 and retinoblastoma protein. Epidemiological factors, diagnostic tools, and management of the disease are examined in this manuscript, as are the vaccines currently marketed to protect against viral infection. We offer insights into ongoing research on the roles that oxidative stress and microRNAs play in cervical carcinogenesis since such studies may lead to novel methods of diagnosis and treatment. Several of these topics are surfacing as being critical for future study. One particular area of importance is the study of the mechanisms involved in the modulation of infection and cancer development at cervical sites. HPV-induced cancers may be vulnerable to immune therapy, offering the chance to treat advanced cervical disease. We propose that oxidative stress, mRNA, and the mechanisms of HPV infection will be critical points for HPV cancer research over the next decade.